Effects of dissolved gas on the nucleation and growth of ice crystals in freezing droplets. (March 2022) - Li, Yingling; Li, Minxia; Dang, Chaobin; Liu, Xuetao
Highlights: Bubble formation process in freezing droplets were experimentally investigated. Effect of the dissolved gas on the nucleation and growth of ice crystals were studied. A quantitative analysis of the tip angles of frozen droplet was proposed. Effect of the dissolved gas on the initial frost crystal was experimentally investigated. Abstract: The solidification process of water (liquid) can cause an intricate deformation of its structures, from the complex of ice crystals to dendritic frost crystal growth. The dissolved gas in water (liquid) is rejected and accumulated ahead of the ice-water interface during solidification and the resulting bubbles are incorporated into the growing ice crystal. In this study, the bubble formation process and the effect of the dissolved gas on the nucleation and growth of ice crystals in freezing droplets at various gas concentrations were experimentally investigated. The dissolved gas acted as a heterogeneous medium, and promoted the nucleation of the liquid droplets. Compared with the pure solid ice crystal, during the freezing process, the existence of bubbles altered the solid-liquid density ratio and the shape of the droplets. Coupled with experimental observations, a quantitative analysis of the tip angles was proposed to elucidate this influence, which indicated that the tip angle of the frozen ice droplet decreased with the gas concentration, and promoted the growth of the initial frost crystal. Graphical abstract: Image, graphical abstract